Pendidikan Karakter Berbasis Sunnah Nabi - Hairuddin, Hairuddin (Al-Ulum, 2013)
This paper elaborates about educational character based on Prophet Muhammad Saw’s traditions. Some problems are arising on our youth generation, such as narcotic distribution, free sex, students fighting, etc., make us and education practical to find a solution in order to save the generation. Finding solution for the problems have been mentioned above is not too difficult, since we are serious to study and understand Islam teaching. It is because one of the main objectives of delegating Prophet Muhammad Saw is to repair human character. The Prophet Muhammad Saw) that all his attitude and behaviour are reflection from Al Qur’an has been succeed to build one generation is known as Rabbani, namely the generation who perfect on their belief of God and their character. The qualified education theory is valid theory logically and comes from outdebating source or reference, and the theory is only met in the Quran and the traditions of the prophet Muhammad Saw which are the main theme of this journal.